Edaravone reduces the markers of oxidative stress and neuroinflammation in neocortex of rats with acute intracerebral hemorrhage and type 2 diabetes mellitus - V. L. Holubiev; A. E. Lievykh; V. A. Tkachenko; Yu. V. Kharchenko; V. I. Zhyliuk (The Ukrainian Biochemical Journal)
Type 2 diabetes mellitus (T2DM) is associated with a higher incidence of hemorrhagic stroke in a severe form. The aim of this study was to estimate the markers of oxidative stress and neuroinflammation in the brain of rats with acute intracerebral hemorrhage (ICH) and T2DM after treatment with edaravone. T2DM was induced by a single intraperitoneal injection of nicotinamide/streptozotocin, ICH – by stereotactic microinjection of bacterial collagenase. Rats were randomized into four groups: 1 – intact control; 2 – T2DM; 3 – T2DM+ICH; 4 – T2DM+ICH+edaravone 6 mg/kg/day. Edaravone (a drug to treat neural injury after acute cerebral ischemic stroke) was administered intraperitoneally for 10 days starting from the 60th day after diabetes mellitus induction and 30 min after ICH induction. Brain homogenates were assessed for the content of advanced glycation end products (AGEs) and advanced oxidation protein products (AOPPs). The levels of TNF-α and 8-hydroxy-2′-deoxyguanosine (8-OHdG) were measured with ELISA. The increased content of 8-OHdG and TNF-α in brain homogenates of animals of T2DM group compared to the control was shown. It was revealed that in brain homogenates of animals of T2DM+ICH group the content of these markers significantly exceeds that for T2DM group, and in addition, an elevated AOPPs level was observed. Our results demonstrated that edaravone prevented the elevation of TNF-α level, reduced oxidative DNA damage by decreasing 8-OHdG content, and attenuated the formation of AGEs and AOPPs in the brains of experimental animals. These findings suggest that edaravone may have therapeutic potential in diabetic patients with acute ICH.